Expertise, Motivasi Dosen dan Metode Pembelajaran: Pengukuran Kemampuan Dosen untuk Memahami Kesesuaian Prestasi Mahasiswa terhadap Kompetensi Lulusan - Sofian, Erza; Pertiwi, Asri (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
The purpose of this research is to measure lecture capabilities in 3 variables, motivation, expertise/professionalism and methods in contributing to lecturing/education system. The measure is done by using decision tree technique / model for classifying the variables and grouping the objects into several groups. This method/approach can help in exploring the data and decide the selected relationship between variable input and target so that the method can be dimension as indicator in measuring variables to lecturer capabilities that are seen from motivation, expertise, and lecturing system. In increasing productivity in lecturing, researcher mainly focus on lecture capabilities in motivation, expertise and lecturing system as the basis for research object. By illustrating research model from several factors that can influence increasing student achievement/performance in STIMIK ESQ and the result from this research will produce recommendation in education/lecturing system that can be used as guidance in the future.